If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5v + -2) + v = 2(v + 9) Reorder the terms: -3(-2 + 5v) + v = 2(v + 9) (-2 * -3 + 5v * -3) + v = 2(v + 9) (6 + -15v) + v = 2(v + 9) Combine like terms: -15v + v = -14v 6 + -14v = 2(v + 9) Reorder the terms: 6 + -14v = 2(9 + v) 6 + -14v = (9 * 2 + v * 2) 6 + -14v = (18 + 2v) Solving 6 + -14v = 18 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. 6 + -14v + -2v = 18 + 2v + -2v Combine like terms: -14v + -2v = -16v 6 + -16v = 18 + 2v + -2v Combine like terms: 2v + -2v = 0 6 + -16v = 18 + 0 6 + -16v = 18 Add '-6' to each side of the equation. 6 + -6 + -16v = 18 + -6 Combine like terms: 6 + -6 = 0 0 + -16v = 18 + -6 -16v = 18 + -6 Combine like terms: 18 + -6 = 12 -16v = 12 Divide each side by '-16'. v = -0.75 Simplifying v = -0.75
| 2p-30=-4p+6 | | 360=h(11+7) | | 1k+1=3k-1 | | 8+4(3w-1)=-4(2w-2)+4w | | t-3.2=-8.3 | | 9x^2-35x+18=0 | | 7-2=-10 | | 7+Z=19 | | 11x-12=2x+6 | | 3x-12=8x-6+4 | | 6(v-4)-9=-3(-8v+8)-3v | | 6k=14 | | D-1=-2 | | 8x+6-9x=3-x-15 | | 3=(2-5) | | 20(3y+1)= | | 7z^2+8z+z^3=0 | | 5(5x+1)=8(3x+1) | | -15x+10x=100 | | 2v+34=4(v+9) | | 8-(3-2)=6 | | 4+5x+1-3x=-4+6x+5-5x | | x^3+6x^2-11x+6=0 | | -x^2+10x+25=0 | | 1.12+1.25g=8.63 | | c=20 | | 34-19=3(x-3) | | 3x-6=5x-19 | | 0.14x+0.07(5000-x)=448 | | -9(u-2)=-5u+14 | | 56=-2(2j+8)-10 | | -3+9=15x-5-14x |